Unlocking earth: One step further towards a conventional use of rammed earth as a building material in Sweden - Olsson, Matilda (My University, 2022)
Earth is a material with excellent health properties, low embodied energy, and the possibility of being indefinitely recyclable. As a structural building material, it has great potential in reducing emissions caused by the building sector. This master’s thesis is exploring the limits of implementing rammed earth in a Swedish context, and how to overcome them through design. Building laws and regulations, climate, costs, and rammed earth knowledge are all topics considered relevant and where the exploration is initiated. Swedish building regulations are in general quite vague, and definite conclusions are hard to make. Most challenges are found when looking at mechanical resistance and durability. There are multiple new, as well as ancient examples around the world proving its potential, though the impact of the Swedish climate, with intense wind and rain, is uncertain due to water solubility. An array of solutions to handle erosion are discussed in this thesis. The procedure of approving new building materials is another challenge, it is currently adapted to conventional industrial materials, and not materials with varying properties like earth. Prefabrication, which already has been initiated on a small scale, can be a solution. It enables careful and frequent monitoring and testing, ensuring good quality. Prefabrication also brings down the costs, making it more time-efficient with fewer in situ manpower hours. With set routines, knowledge will increase which is necessary for the development of rammed earth in Sweden. All challenges in implementing rammed earth in a Swedish context are considered solvable, but the first steps and investments needed are huge in proportion to the lack of demand on the market. The much-needed transition into a more sustainable society is approaching, and with it comes a demand for more sustainable building solutions, where rammed earth is prominent. The investigation is resulting in a redesign of an already existing design, using rammed earth. Details are adapted to the circumstances of each individual element, and the proposal can thereby, be viewed as a compilation of possible wall compositions using rammed earth in a Swedish context.
Keywords: Excavated clay, rammed earth, prefabrication, BBR, erosion